Placebo versus low-dose ketamine infusion in addition to remifentanil target-controlled infusion for conscious sedation during oocyte retrieval: A double-blinded, randomised controlled trial. Issue 9 (September 2018) - Morue, Hélène I.; Raj-Lawrence, Shalini; Saxena, Sarah; Delbaere, Anne; Engelman, Edgard; Barvais, Luc A.
Abstract : BACKGROUND: Currently, there is no gold standard for monitored anaesthesia care during oocyte retrieval. OBJECTIVE: In our institution, the standard is a conscious sedation technique using a target-controlled infusion (TCI) of remifentanil, titrated to maintain a visual analogue pain score less than 30 mm. This protocol is well accepted by patients but is associated with frequent episodes of respiratory depression. The main objective of this study was to evaluate whether the addition of a continuous intravenous infusion of ketamine could reduce these episodes. DESIGN: Controlled, randomised, prospective, double-blinded study. SETTING: The current study was conducted in a tertiary-level hospital in Brussels (Belgium) from December 2013 to June 2014. PATIENTS: Of the 132 women undergoing oocyte retrieval included, 121 completed the study. INTERVENTION: After randomisation, patients received either a ketamine infusion (40 μg kg −1 min −1 over 5 min followed by 2.5 μg kg −1 min −1 ) or a 0.9% saline infusion in addition to the variable remifentanil TCI. MAIN OUTCOME MEASURES: The primary outcome was the number of respiratory depression episodes. Effect site target remifentanil concentrations, side effects, pain score, patient satisfaction and incidence of pregnancy were also recorded. RESULTS: No significant difference in the incidence of respiratory events was noted (pulse oximetry oxygen saturation < 95% was 49% in the ketamine group and 63% in the control group; P = 0.121). No patient required ventilatory support. In the ketamine group, visual analogue pain score and remifentanil concentrations were significantly reduced, but the latter remained above 2 ng ml −1 . Postoperative nausea was less frequent in the ketamine group, 4 versus 15% ( P = 0.038). The addition of ketamine did not influence length of stay nor patient satisfaction. CONCLUSION: The addition of low plasma levels of ketamine to a TCI remifentanil conscious sedation technique did not decrease the incidence nor the severity of respiratory depression. Continuous monitoring of capnography and oxygen saturation is always required. TRIAL REGISTRATION: EUDRACT number 2013-003040-23.